2010
DOI: 10.1007/s10456-010-9196-7
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow cells participate in tumor vessel formation that supports the growth of Ewing’s sarcoma in the lung

Abstract: An MHC-mismatch bone marrow (BM) transplant Ewing's sarcoma mouse model was used to investigate whether BM cells participate in the vessel formation that support Ewing's sarcoma lung metastasis. BM cells from H-2K b/d donor mice were transplanted into sublethally irradiated H-2K d recipient mice. Donor BM cells were identified using the H-2K b marker. Engraftment was confirmed by identifying the H-2K b IL-1β-type specific polymorphism. After engraftment highly lung metastatic TC71-PM4 cells were injected intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…These data confirmed that REST plays a critical role in maintaining and expanding ES tumor vessels that are required for tumor growth. These findings together with our previous studies show that interfering with vascular formation and expansion severely retards not only tumor growth but also metastasis to the lung [16][17][18][19][20][21]. REST is therefore a potential target for ES therapy.…”
Section: Introductionsupporting
confidence: 70%
“…These data confirmed that REST plays a critical role in maintaining and expanding ES tumor vessels that are required for tumor growth. These findings together with our previous studies show that interfering with vascular formation and expansion severely retards not only tumor growth but also metastasis to the lung [16][17][18][19][20][21]. REST is therefore a potential target for ES therapy.…”
Section: Introductionsupporting
confidence: 70%
“…Interestingly, studies in experimental models have indicated that mature pericytes protect endothelial cells against VEGFR-directed therapies [ 22 , 23 ]. The recent demonstration that tumor cells are able to induce pericyte maturation of the neovasculature during early formation of micrometastatic foci [ 24 ] might provide one explanation for the lack of efficacy of bevacizumab in eradicating occult metastatic disease in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that in ES, migration of bone marrow stem cells to the tumor site and differentiation of these cells into pericytes plays a role in the formation of new tumor blood vessels [9][10][11][12][13][14][15]. Interfering with tumor pericyte formation, similar to interfering with endothelial progenitor cells, significantly interfered with tumor vascular expansion, tumor growth and metastases [9][10][11][12][13][14][15][16]. These bone marrow-derived stem cells had migrated into the tumor area in response to VEGF165 and SDF-1 [14,17,18].…”
Section: Introductionmentioning
confidence: 99%